Benziodoxole-Derived Organosulfonates: The Strongest Hypervalent Iodine Electrophiles and Oxidants - Yusubov, Mekhman S.; Postnikov, Pavel; Yoshimura, Akira; Zhdankin, Viktor V. (Synlett, 2020)
This account describes the development of organosulfonyloxy-substituted iodine(III) and iodine(V) benziodoxole derived reagents, which are thermally stable compounds with useful reactivity patterns. Iodine(III) benziodoxoles and pseudobenziodoxoles are powerful electrophiles and mild oxidants toward various unsaturated compounds. In particular, pseudocyclic benziodoxole-derived triflate (IBA-OTf) is an efficient reagent for oxidative heteroannulation reactions. Aldoximes react with nitriles in the presence of IBA-OTf at room temperature to give 1,2,4-oxadiazoles in high yields. Moreover, IBA-triflate is used as a catalyst in oxidative heteroannulations with m-chloroperoxybenzoic acid as the terminal oxidant. The iodine(V) benziodoxole derived tosylates, DMP-tosylate and IBX-tosylate, are superior oxidants for the oxidation of structurally diverse, synthetically useful alcohols, utilized as key precursors in the total syntheses of polyketide antibiotics and terpenes. And finally, the most powerful hypervalent iodine(V) oxidant, 2-iodoxybenzoic acid ditriflate (IBX·2HOTf), is prepared by treatment of IBX with trifluoromethanesulfonic acid. According to the X-ray data, the I–OTf bonds in IBX-ditriflate have ionic character, leading to the high reactivity of this reagent in various oxidations. In particular, IBX-ditriflate can oxidize polyfluorinated primary alcohols, which are generally extremely resistant to oxidation.1 Introduction2 Iodine(III) Benziodoxole Based Organosulfonates3 Pseudocyclic Iodine(III) Benziodoxole Triflate (IBA-triflate)4 Pseudocyclic Iodine(III) Benziodoxole Tosylates5 Iodine(V) Benziodoxole Derived Tosylates6 Iodine(V) Benziodoxole Derived Triflate (IBX-ditriflate)7 Conclusions
Keywords: hypervalent iodine; iodine; iodonium; 2-iodosylbenzoic acid (IBA); 2-iodoxybenzoic acid (IBX); oxidation